Identifikasi Bawang Merah dan Bombay dengan Pendekatan Radial Basis Function Neural Network (RBFNN) - Agusriandi, Agusriandi; Elihami, Elihami; Widiawati, Wilda (STMIK Budi Darma, 2020)
A fact that identification in a human knowledge is very important role. Identification is able to summarize the knowledge, so it is easy to understand. Therefore, the classification of leek or red onion is an interesting study because the similarity of physical appearance of morphology between these two commodities is difficult to distinguish directly. This research tries to detect the difference between Bombay onion and red onion by using neural network with RGB color feature extraction method and gabor filter. The results of the detection are able to classify the types of onions, whether the onion is included in the type of leek or red onion. Many methods can be used to perform classification, one of which is Radial Basis Function Neural Network (RBFNN). After performing simulation with Matlab program, 100 images that become test data can be recognized perfectly.